2011
DOI: 10.1200/jco.2010.32.0432
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Negative Sentinel Nodes Accurately Predict Absence of Lymph Node Metastasis in Early Cervical Cancer: Results of the SENTICOL Study

Abstract: Combined labeling for node mapping was associated with high rates of SLN detection and with high sensitivity and NPV for metastasis detection. However, SLN biopsy was fully reliable only when SLNs were detected bilaterally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
263
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(280 citation statements)
references
References 25 publications
(13 reference statements)
7
263
0
10
Order By: Relevance
“…For the remaining studies, the full text was read. Finally, a total of 17 studies were included in the analysis, involving a total of 1,112 patients (5,6,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The study selection process is summarized in Fig.…”
Section: Study Selection and Descriptionmentioning
confidence: 99%
“…For the remaining studies, the full text was read. Finally, a total of 17 studies were included in the analysis, involving a total of 1,112 patients (5,6,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The study selection process is summarized in Fig.…”
Section: Study Selection and Descriptionmentioning
confidence: 99%
“…As a matter of fact, looking at the official international literature, the frequency of a correct SLN identification really varies from one approach used to another and from a working team to another. In this context of very heterogeneous data, referring to the French and American studies that report the best results, the chance of optimal SLN identification is not superior to 76.5% 13, 15. These results significantly impact the overall sensitivity of the procedure, as a failure in SLN mapping in one or both the hemipelvis leaves the “negative” side completely uninvestigated.…”
Section: Discussionmentioning
confidence: 98%
“…Despite large studies have demonstrated a good diagnostic performance of SLN biopsy in cervical cancer patients, with a NPV ranging from 94.3% to 98.2%, one of the main concerns about its full adoption is the relatively low detection rate of the technique 11, 13, 20, 21, 22. As a matter of fact, looking at the official international literature, the frequency of a correct SLN identification really varies from one approach used to another and from a working team to another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Other authors have demonstrated a 94% rate of detection of sentinel lymph nodes associated with sensitivity and negative predictive value of 100%, for tumors less than 2 cm. 17 The recent study SENTICOL 18 , in which SLB was carried out in a uniform manner by experienced surgeons, combining techniques that utilize blue dye and lymphoscintigraphy with technetium (Tc99), demonstrated a sensitivity of 92% and obtained ideal mapping in 75% of patients. These authors concluded that when utilizing the two techniques combined, a negative result in the sentinel lymph nodes on both sides indicates the absence of metastatic disease, with a negative predictive value of 98.2%.…”
Section: Lymph Nodesmentioning
confidence: 99%